Model-based real-time thermal fault diagnosis of Lithium-ion batteries. (November 2016) - Dey, Satadru; Biron, Zoleikha Abdollahi; Tatipamula, Sagar; Das, Nabarun; Mohon, Sara; Ayalew, Beshah; Pisu, Pierluigi
Abstract: Ensuring safety and reliability is a critical objective of advanced Battery Management Systems (BMSs) for Li-ion batteries. In order to achieve this objective, advanced BMS must implement diagnostic algorithms that are capable of diagnosing several battery faults. One set of such critical faults in Li-ion batteries are thermal faults which can be potentially catastrophic. In this paper, a diagnostic algorithm is presented that diagnoses thermal faults in Lithium-ion batteries. The algorithm is based on a two-state thermal model describing the dynamics of the surface and the core temperature of a battery cell. The residual signals for fault detection are generated by nonlinear observers with measured surface temperature and a reconstructed core temperature feedback. Furthermore, an adaptive threshold generator is designed to suppress the effect of modelling uncertainties. The residuals are then compared with these adaptive thresholds to evaluate the occurrence of faults. Simulation and experimental studies are presented to illustrate the effectiveness of the proposed scheme. Highlights: A real-time diagnostic scheme for battery thermal faults is proposed. A thermal model that captures core and surface temperature of the battery is used. The scheme detects and isolates thermal faults affecting the core and surface temperature. Proposed diagnostic scheme is evaluated via simulation and experimental studies.